A numerical parametric study of solidification inside a rectangular enclosure - Chua, Song Teck. (2009)
This project focuses on the numerical study of solidification of pure material in an enclosure. The numerical model is based on the enthalpy formulation and SIMPLE algorithm. The numerical solution is compared with analytical data in a one-dimensional solidification problem. The results show a good agreement between the analytical data and numerical solution.